2007
DOI: 10.5713/ajas.2007.775
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of Different Soy Protein Sources on Growth Performance, Nutrient Digestibility and Intestinal Morphology in Weaned Pigs

Abstract: To elucidate the efficacy of different soy protein sources on piglet's performance, a total of 280 weaned piglets (Duroc×Yorkshire×Landrace, 23±3 d of age, 5.86±0.45 kg initial BW) were allotted to 5 treatment diets comprising soybean meal (SBM), soy protein concentrate (SPC), Hamlet protein (HP300), fungal (Aspergillus oryzae) fermented soy protein (FSP-A), and fungal plus bacterial (A. oryzae+Bacillus subtilis) fermented soy protein (FSP-B), respectively. Experimental diets for feeding trial were formulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
59
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(79 citation statements)
references
References 24 publications
15
59
3
Order By: Relevance
“…The SID in SBM hp , reported herein, are in good agreement with those reported by Yang et al (2007), whereas Walker et al (1986) reported up to 17 percentage units greater SID. For soy protein concentrate, reports on SID of indispensable AA vary between 94% and 100% (Walker et al, 1986) and between 81% and 91% (Yun et al, 2005;Yang et al, 2007). Moreover, Yun et al (2005) and Yang et al (2007) determined up to 6 percentage units smaller SID of indispensable AA in soy protein concentrate compared with the present study, whereas Walker et al (1986) reported up to 17 percentage units greater SID of indispensable AA in soy protein concentrate than the present study.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The SID in SBM hp , reported herein, are in good agreement with those reported by Yang et al (2007), whereas Walker et al (1986) reported up to 17 percentage units greater SID. For soy protein concentrate, reports on SID of indispensable AA vary between 94% and 100% (Walker et al, 1986) and between 81% and 91% (Yun et al, 2005;Yang et al, 2007). Moreover, Yun et al (2005) and Yang et al (2007) determined up to 6 percentage units smaller SID of indispensable AA in soy protein concentrate compared with the present study, whereas Walker et al (1986) reported up to 17 percentage units greater SID of indispensable AA in soy protein concentrate than the present study.…”
Section: Resultssupporting
confidence: 81%
“…For piglets, reports on SID of indispensable AA in soy protein concentrate and soybean meal are not consistent between studies. For example, SID of indispensable AA in soybean meal range from 86% to 98% and from 76 to 86% in studies by Walker et al (1986) and Yang et al (2007), respectively. The SID in SBM hp , reported herein, are in good agreement with those reported by Yang et al (2007), whereas Walker et al (1986) reported up to 17 percentage units greater SID.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, despite the positive influence of spray-dried plasma on piglet performance in the present study, the diet containing 5% BP did not lead to the best performance; however, the diet containing 2.5% BP and 2.5% SPC led to the best performance. This can be explained by the reduced stimulation of the immune system caused by the presence of spray-dried plasma and by the protein quality of the soy protein concentrate, together with its high digestibility, as described by Yang et al (2007).…”
Section: Resultsmentioning
confidence: 99%
“…Soy protein concentrate (SPC), which does not contain antinutritional factors, such as allergenic proteins and oligosaccharides that are present in soybean meal, is effective in improving the performance of post-weaning piglets (Lenehan et al, 2007;Yang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%